Diplomasi Islam Nusantara Berbasis Pesantren: Peran Strategis Nahdlatul Ulama dalam Agenda Perdamaian Global - M. Sholahul 'Am Noto Buwono; Imam Syafi’i; Khotimah Suryani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This article examines pesantren-based Islam Nusantara diplomacy and the strategic role of Nahdlatul Ulama (NU) in the global peace agenda. Using a qualitative approach through library research and document analysis, the study explores how pesantren function not merely as traditional Islamic educational institutions, but as social, cultural, and epistemic foundations for religious diplomacy. The findings show that pesantren serve as laboratories for the formation of moderate Islamic values, including tawasut, tawazun, tasamuh, and taadul, which are then articulated by NU through cultural diplomacy, institutional forums such as the R20, PCINU diaspora networks, and interfaith engagement. The study argues that NU’s diplomacy operates through a hybrid religious diplomacy model that combines pesantren values, organizational legitimacy, global forums, grassroots networks, and digital narratives. This model contributes to global peacebuilding by offering an alternative Islamic narrative rooted in moderation, local wisdom, moral authority, and social coexistence. The article also highlights the need to strengthen pesantren capacity in intercultural communication, digital literacy, peace studies, and international networking to ensure more sustainable and measurable contributions to global peace.